Struktur Histopatologi Tangkai Daun Jeruk Siam (Citrus nobilis L. var. microcarpa) Terinfeksi Citrus Vein Phloem Degeneration (CVPD) pada Tingkat Serangan Ringan dan Berat - TRIAN WANGSA PURWANTO; MADE SRITAMIN; NI LUH MADE PRADNYAWATHI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
Histophatology Structure of Siam Citrus Petiole (Citrus nobilis L. var. microcarpa) Infected by Citrus Vein Phloem Degeneration (CVPD) at Mild and Severe Attack Rates The main cause of decreasing the production of Citrus nobilis L. var. microcarpa in Indonesia is the presence of CVPD disease (Citrus Vein PhloemDegeneration). Citrus nobilis L. var. microcarpa infected by CVPD showing anatomic and morphological changes. The main objective of this study was todetermine anatomic changes in petiole tissue of Citrus nobilis L. var. microcarpa infected by CVPD at the level of mild and severe attacks. The research wasconducted in Citrus field, Kintamani, Bangli-Bali and Biomolecular and Genetic Resources Laboratory, Faculty of Agriculture, Udayana University in August September 2018. The result for visual observation showed that the presentasion of CVPD symptoms in the field was 46% and attack intensity was 39.6%. Samples were identified using PCR metod with O11 and O12c markers. DNA visualization amplified on 1% agarose showed appearing of DNA band for samples with mild and severe attack rates. Samples gave positive reaction to Liberibacter asiaticus. It showed that the samples were positive infected by CVPD disease. Preparations of petioles were made to observe the histological structure microscopically. The result showed that there were changes on histological structure of petioles infected CVPD. Petioles infected CVPD at mild symptom and severe symptom showing cell wall thickening on epidermis, shape changes on cortex and there were an accumulation of starch, lysis and necrosis showing on floem with severe attack rate, and there were stretching between xylem cells.